Prognostic and clinicopathological value of Ki-67 expression in patients with nasopharyngeal carcinoma: a meta-analysis. (September 2020) - Shi, Zhaohui; Jiang, Weihong; Chen, Xiaodong; Xu, Min; Wang, Xiaocheng; Zha, Dingjun
Background: This meta-analysis aimed to identify the prognostic role of Ki-67 in patients with nasopharyngeal carcinoma (NPC). Methods: Relevant studies were retrieved in the PubMed, Embase, Web of Science, and Cochrane Library databases up to November 2019. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to estimate the association between Ki-67 expression and survival outcomes. Combined odds ratios (ORs) and 95% CIs were measured as effect size on the association between Ki-67 expression and clinical factors. Results: A total of eight studies involving 936 patients with NPC were included in this meta-analysis. The pooled HR indicated that Ki-67 expression was significantly associated with poor overall survival (HR = 2.86, 95% CI = 1.91–4.27, p < 0.001), progression-free survival (HR = 1.78, 95% CI = 1.15–2.74, p = 0.009), and distant metastasis-free survival (HR = 1.65, 95% CI = 1.15–2.36, p = 0.007). However, there was no significant correlation between Ki-67 expression and local recurrence-free survival (HR = 1.07, 95% CI = 0.54–2.14, p = 0.843). Ki-67 overexpression was associated with higher T stage (OR = 1.48, 95% CI = 1.00–2.20, p = 0.052), and the relationship between Ki-67 expression and advanced stage was nearly significant (OR = 2.25, 95% CI = 0.99–5.14, p = 0.054). However, high Ki-67 expression was not significantly correlated with sex, age, N stage, or histological type. Conclusion: This meta-analysis demonstrated that Ki-67 overexpression was a significant marker for poor prognosis in patients with NPC. Ki-67 should be recommended as a useful index for prognostication in patients with NPC.